Spatiotemporal interactions between audition and touch depend on hand posture. - Sanabria, D; Soto-Faraco, S; Spence, C (2005)
We report two experiments designed to assess the consequences of posture change on audiotactile spatiotemporal interactions. In Experiment 1, participants had to discriminate the direction of an auditory stream (consisting of the sequential presentation of two tones from different spatial positions) while attempting to ignore a task-irrelevant tactile stream (consisting of the sequential presentation of two vibrations, one to each of the participant's hands). The tactile stream presented to the participants' hands was either spatiotemporally congruent or incongruent with respect to the sounds. A significant decrease in performance in incongruent trials compared with congruent trials was demonstrated when the participants adopted an uncrossed-hands posture but not when their hands were crossed over the midline. In Experiment 2, we investigated the ability of participants to discriminate the direction of two sequentially presented tactile stimuli (one presented to each hand) as a function of the presence of congruent vs incongruent auditory distractors. Here, the crossmodal effect was stronger in the crossed-hands posture than in the uncrossed-hands posture. These results demonstrate the reciprocal nature of audiotactile interactions in spatiotemporal processing, and highlight the important role played by body posture in modulating such crossmodal interactions.